Meat production characteristics of Egyptian Baladi and Angora goats - Latif, M.G.A.; Abdelsalam, M.M.; Abd el-Aziz, N.M. (Elsevier, 1987)
Fifteen Baladi and 20 Angora intact males raised together from birth until 8 months of age were grown on a commercial coneentrate mixture fed at the rate of 0.6 kg/head/day with chopped wheat straw fed at 0.5 kg/head/day for 14 weeks. Body measurements were taken before slaughter and carcass measurements and offal eights after it. The right sides of all carcasses were dissected into cuts, weighed and deboned. Fat was separated from the 9-10-11 rib joints and estimated. The two breeds did not significantly differ in birth weight, weaning weight. carcass weight, dressing percentage, most body measurements, all carcass measurements and most offal weights. Significant differences are only found in body length, height at withers, weights of spleen and kidney fat. However, the Baladi had significantly heavier loin and shloulder (p< 0.01) and breast and flank (p< 0.05) than the Angora which had heavier legs (p< 0.05), The carcasses of the two breeds had very similar percentages of edible meat (68.38 versus 68.65),lean (57.47 verus 57.38) and fat in the rib joint (10.91 versus 11.27).